2010
DOI: 10.1128/jvi.01053-10
|View full text |Cite
|
Sign up to set email alerts
|

CD1d, a Sentinel Molecule Bridging Innate and Adaptive Immunity, Is Downregulated by the Human Papillomavirus (HPV) E5 Protein: a Possible Mechanism for Immune Evasion by HPV

Abstract: CD1d and CD1d-restricted natural killer T (NKT) cells serve as a natural bridge between innate and adaptive immune responses to microbes. CD1d downregulation is utilized by a variety of microbes to evade immune detection. We demonstrate here that CD1d is downregulated in human papillomavirus (HPV)-positive cells in vivo and in vitro.CD1d immunoreactivity was strong in HPV-negative normal cervical epithelium but absent in HPV16-positive CIN1 and HPV6-positive condyloma lesions. We used two cell lines for in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 45 publications
1
85
0
4
Order By: Relevance
“…and a stably transfected HPV-negative cervical cancer cell line, C33A (C33A/CD1d), HPVs have been found to downregulate CD1d expression by E5 protein mediated disruption of ER traffic. Accordingly, it has been suggested that the decreased CD1d expression in the presence of HPV E5 may facilitate the virus infected cells to evade protective immunological surveillance [97].…”
Section: Natural Killer (Nk) Cell Response During Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…and a stably transfected HPV-negative cervical cancer cell line, C33A (C33A/CD1d), HPVs have been found to downregulate CD1d expression by E5 protein mediated disruption of ER traffic. Accordingly, it has been suggested that the decreased CD1d expression in the presence of HPV E5 may facilitate the virus infected cells to evade protective immunological surveillance [97].…”
Section: Natural Killer (Nk) Cell Response During Viral Infectionmentioning
confidence: 99%
“…Measles virus [128] Proteases targeting signal transduction Block IFN induction by affecting molecules of the innate immune pathways HAV, HCV [110] Degradation of cellular TRIF Replication and transcription activator (RTA) degrades TRIF KSHV [2] CD1d down regulation Viral protein E5 targets CD1d (a sentinel molecule bridging innate and adaptive immunity) by inhibiting calnexin-related CD1d trafficking HPV [97] Science and Technology, Govt. of India.…”
Section: Concluding Remarkmentioning
confidence: 99%
“…The immunoevasive targeting of CD1d is not unique to C. trachomatis. We have also shown that cell surface expression of CD1d is reduced in vitro and in vivo in human papillomavirus (HPV)-positive cells (Miura, Kawana et al 2010). This effect can be isolated to the presence of the E5 proteins of HPV subtype 6 and HPV subtype 16, it occurs at a post-transcriptional level and it is mediated by proteasomal degradation.…”
Section: Production Of Cpaf and Effects On Cd1dmentioning
confidence: 99%
“…E7 expression is nevertheless associated with impairment of IFN-gama-induced enhancement of presentation of endogenous antigen to cytotoxic T lymphocytes (Zhou et al, 2011). Further mechanism of HPV-mediated immune escape involve viral proteins: HPV E7 has high and widespread similarity to several humans proteins, causing a limited immunogenicity (Natale et al, 2000); E6 can downregulate IL-18 expression (Cho et al, 2001); E5 mediate acidification of endossomes, affecting antigen processing and presentation in antigen presentation cells (Straight et al, 1995); E5 also downregulate CD1d, a MHC I-like glycoprotein that presents self or microbial lipid antigen to natural killer -the downregulation of this molecule is utilized by a variety of microbes to evade immune detection (Miura et al, 2010). Finally, natural killer (NK) cell activity is also reduced in patients with HR-HPV infection (Stanley, 2009a;O´Brien and Campos, 2002).…”
Section: Mechanism Of Immune Evasionmentioning
confidence: 99%